Photochemically prepared monodisperse gold nanoparticles as doxorubicin carrier and its cytotoxicity on leukemia cancer cells - Dizman, H. Mirac; Eroglu, Gunes Ozen; Kuruca, Serap Erdem; Arsu, Nergis (SPRINGER HEIDELBERG, 2021)
In this study, a new thioxanthone derivative called 3,3 '-disulfanediylbis(1-hydroxy-9H-thioxanthen-9-one) was utilized in situ for the photochemical synthesis of monodisperse gold nanoparticles, and simple characterization was achieved by formation of a typical surface plasmon resonance band of gold nanoparticles at 535 nm accompanied by a nice pink color. Dynamic light scattering method was employed for determination of the size of the in situ-prepared gold nanoparticles and, with good polydispersity value at around 30 nm, it was in good agreement with the surface plasmon resonance band. After successful preparation of gold nanoparticles, a well-known cancer drug, doxorubicin, at different amounts was loaded onto prepared gold nanoparticles. The adsorbed and released doxorubicin amount onto the gold nanoparticles was calculated by a fluorescence spectrophotometer using a calibration curve. Doxorubicin-loaded gold nanoparticles were examined using a MTT assay for both HL-60 and K562 leukemia cancer cells and HUVEC cells, and 5 mu L doxorubicin-loaded gold nanoparticles significantly reduced cell viability. In normal HUVEC cells, 5 mu L doxorubicin-loaded gold nanoparticles were found less cytotoxic compared to doxorubicin alone. The data obtained in this study showed that gold nanoparticles loaded with 5 mu L doxorubicin are much more effective than doxorubicin used alone in cancer treatment.
Keywords: Photochemistry; Gold nanoparticles; Thioxanthone-disulfide; Drug delivery; Anticancer drug; FREE-RADICAL POLYMERIZATION; PHOTOINITIATOR; CHEMOTHERAPY; PARTICLES; MATRIX; TUMOR; Science & Technology - Other Topics